Analysis of comparative sequence and genomic data to verify phylogenetic relationship and explore a new subfamily of bacterial lipases - Masomian, Malihe; Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Basri, Mahiran (Public Library of Science, 2016)
Thermostable and organic solvent-tolerant enzymes have significant potential in a wide range of synthetic reactions in industry due to their inherent stability at high temperatures and their ability to endure harsh organic solvents. In this study, a novel gene encoding a true lipase was isolated by construction of a genomic DNA library of thermophilic Aneurinibacillus thermoaerophilus strain HZ into Escherichia coli plasmid vector. Sequence analysis revealed that HZ lipase had 62% identity to putative lipase from Bacillus pseudomycoides. The closely characterized lipases to the HZ lipase gene are from thermostable Bacillus and Geobacillus lipases belonging to the subfamily I.5 with ≤ 57% identity. The amino acid sequence analysis of HZ lipase determined a conserved pentapeptide containing the active serine, GHSMG and a Ca2+-binding motif, GCYGSD in the enzyme. Protein structure modeling showed that HZ lipase consisted of an α/β hydrolase fold and a lid domain. Protein sequence alignment, conserved regions analysis, clustal distance matrix and amino acid composition illustrated differences between HZ lipase and other thermostable lipases. Phylogenetic analysis revealed that this lipase represented a new subfamily of family I of bacterial true lipases, classified as family I.9. The HZ lipase was expressed under promoter Plac using IPTG and was characterized. The recombinant enzyme showed optimal activity at 65°C and retained ≥ 97% activity after incubation at 50°C for 1h. The HZ lipase was stable in various polar and non-polar organic solvents.